2021
DOI: 10.1021/acsomega.1c03577
|View full text |Cite
|
Sign up to set email alerts
|

Computational Appraisal of Silver Nanocluster Evolution on Epitaxial Graphene: Implications for CO Sensing

Abstract: Early stages of silver nucleation on a two-dimensional (2D) substrate, here, monolayer epitaxial graphene (MEG) on SiC, play a critical role in the formation of application-specific Ag nanostructures. Therefore, it is of both fundamental and practical importance to investigate the growth steps when Ag adatoms start to form a new phase. In this work, we exploit density functional theory to study the kinetics of early-stage nuclei Ag n (n = 1–9) assembly of Ag nanoparticles on MEG. We find that the Ag1 monomer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
5
9
0
Order By: Relevance
“…Density functional theory (DFT) calculations of the diffusion barrier for Ag/C(0001) from the literature report a diffusion barrier between 0.3 and 7.6 kJ/mol. 24,50,70 The value for E diff reported here falls within this range.…”
Section: Experimental Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…Density functional theory (DFT) calculations of the diffusion barrier for Ag/C(0001) from the literature report a diffusion barrier between 0.3 and 7.6 kJ/mol. 24,50,70 The value for E diff reported here falls within this range.…”
Section: Experimental Methodssupporting
confidence: 71%
“…51 Another study found an energy change of −224 to −229 kJ per mole of Ag atoms for n × Ag(gas) → Ag n (adsorbed) with n = 7−9 for pseudoepitaxial growth of 2D Ag on graphene/SiC(0001) (up from only −35 and −111 kJ/mol at n = 1 and 2, respectively). 50 These can be compared with the measured heats of adsorption in the first pulses of our experiments where the first pulse at 300 K forms clusters of ∼26 atoms (on average) and an average heat of adsorption of 230 kJ/mol, and the first two pulses at 100 K form clusters of ∼9 and ∼30 atoms, respectively, with heats of adsorption of 223 and 207 kJ/mol, respectively. The differences between our experimental results and those calculations could be attributed to any of the following reasons: (1) the larger cohesive energy for the larger particles we studied, (2) stabilization of particles in our experiments by defect sites in the first pulse at 100 K, (3) stabilization of particles in our experiments due to longrange attractive interactions with the underlying Ni(111) substrate, or (4) intrinsic errors in their DFT calculations or our experiments.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…30,66 We found an adsorption energy of the cluster on the Gr/Ru substrate of 2.32 eV, in agreement with the energy obtained for similar Ag clusters on a graphene/SiC substrate. 67 We used the calculated core-electron binding energies to t the spectrum in Fig. 2(a) with a Doniach-Šunjić lineshape obtaining a Lorentzian (L) to Gaussian (G) width ratio of 0.3 : 0.7, a value consistent with a similar study on Ag nanoparticles with diameters below 2 nm, 57 and an asymmetry parameter a ¼ 0.09.…”
Section: Resultssupporting
confidence: 69%
“…This case can be, to some extent, referred to as water intercalation beneath graphene. We employed double-ζ polarized (DZP) basis set with an energy shift of 200 meV to perform geometric optimization.As was shown in previous work, the DZP basis set is good enough to provide reasonable results for graphene-based systems, including metal–graphene interface. Force tolerance was set to 0.02 eV/Å.…”
Section: Theoretical Modelingsupporting
confidence: 61%